THE LOOK OF THE PHYSICAL EDUCATION IN THE PROJECT CRIANÇAS DE CANUDOS: THE EXPERIENCE OF UNIVERSITY CENTER FEEVALE (Fiep Bulletin - online, 2014)
The Project “Crianças de Canudos" started its activities in 2000, having for objective to provide a conscientious exercise of citizenship and social inclusion, in order to ensure the access and permanence in school of the children and adolescents from Canudos. This project has been created by Physical Education faculty. It offers unique opportunity to express the human movement, in search of child development and communitarian values as well as improvements in quality of life. In addition, this project proposes actions to encourage the development of individuals as a whole, promoting personal autonomy and social inclusion. Thus, it ends up contemplating educative, social, cultural, scientific, and technological dimensions. In this way, in 2007 the fields of Psychopedagogy/Pedagogy, Art therapy, Psychology and Phonoaudiology got involved in it. Undoubtedly, this university extension proposal has been an effective service for academic formation, a privileged locus of knowledge production. The project, throughout its existence, has been a space for pedagogical practices, putting professors/teachers and students/pupils in direct contact with different people in their social relations. We observe that there has been an impressive improvement in the partner-affective relations and in the school performance of the children involved in the project. At last, it has become a space for education, research and extension service, what can be seen in final papers and scientific conferences, such as Salão de Extensão. All of this provides the students to have practical field knowledge, in such way that it is possible to create an articulation between theoretical, technical and scientific aspects that lead to a more humanitarian education.
Keywords: Physical Education; University Extension; Social Vulnerability